Improving Student Learning Outcomes in Islamic Religious Education Learning with the Ice Breaking Method: Classroom Action Research at Elementary School - Hazrullah; Chasanah, Nur (MADINA : Journal of Islamic Studies, 2024)
Teachers play a very important role in efforts to achieve learning objectives. Various methods are used only to help students understand the learning concepts given. This study aims to improve student learning outcomes in Islamic religious education learning. By using the ice breaking method. This study is a classroom action research. The subjects of the study were elementary school students. The data collection techniques used were observation and tests. The data were then analyzed using descriptive statistical techniques. The results of the study showed that the ice breaking method can improve student learning outcomes in Islamic religious education learning. Therefore, the ice breaking method can be used as an alternative in efforts to improve elementary school student learning outcomes.